THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY (CSR), INTELLECTUAL CAPITAL, AND INSTITUTIONAL OWNERSHIP ON THE FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) - Aisidah, Suffi Natul; Widodo, Heri (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the effect of Corporate Social Responsibility, Intellectual Capital, and Institutional Ownership on Financial Performance. Method: This study uses quantitative methods and secondary data sources with mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023 as the object of study. The sampling technique used purposive sampling, which is a technique of sampling based on specific criteria, resulting in 11 companies with a total of 33 sample data. Data analysis was performed using multiple linear regression with SPSS 25 software. Results: The results of the study show that: (1) Corporate Social Responsibility does not affect financial performance, (2) Intellectual Capital affects financial performance, and (3) Institutional ownership has a positive effect on financial performance in mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023. Novelty: The novelty of this study lies in its integrated examination of Corporate Social Responsibility, Intellectual Capital, and Institutional Ownership simultaneously in predicting financial performance, specifically within mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. This research provides updated empirical evidence by combining these three determinants in one model and focusing on a post-pandemic dataset, which has rarely been explored in previous studies on the Indonesian mining sector.